O discurso midiático sobre mudanças climáticas: análise da cobertura ambiental de o Liberal e Folha de São Paulo - SILVA, André Luiz Palmeira da (Universidade Federal do Pará, 2019)
The study objective consisted of analyzing the discourse of climate change produced by O Liberal and Folha de S. Paulo newspapers in their coverage of the environment in 2015, when the Paris Climate Conference, also known as COP-21, was held. A comparative analysis among the discourses of the newspapers was performed, embracing the same period and using the same theoretical-methodological reference, which presents as main basis the Semiology of Social Discourse, through concepts such as Polyphony. In order to define our scope, we approached the work of authors such as Eliseo Verón and Mikhail Bakhtin. The research methodology is anchored in the Discourse Analysis of French strand. The concept of Discursive Formation, by Michel Foucault, was also employed. In order to operationalize our methodology, we referred to the online platform of the respective newspapers to consult the editions and analyze the journalistic texts. In total, 38 texts of Folha de S. Paulo and 27 texts of O Liberal newspaper were analyzed.